2017
DOI: 10.1038/srep44460
|View full text |Cite
|
Sign up to set email alerts
|

Restoring the impaired cardiac calcium homeostasis and cardiac function in iron overload rats by the combined deferiprone and N-acetyl cysteine

Abstract: Intracellular calcium [Ca2+]i dysregulation plays an important role in the pathophysiology of iron overload cardiomyopathy. Although either iron chelators or antioxidants provide cardioprotection, a comparison of the efficacy of deferoxamine (DFO), deferiprone (DFP), deferasirox (DFX), N-acetyl cysteine (NAC) or a combination of DFP plus NAC on cardiac [Ca2+]i homeostasis in chronic iron overload has never been investigated. Male Wistar rats were fed with either a normal diet or a high iron (HFe) diet for 4 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 76 publications
1
31
1
Order By: Relevance
“…The lack of difference in total non-ferritin-bound iron observed between NAC, NAC + DFO and DFO pre-treatments suggests that NAC possesses some inherent iron chelator capacity. This is consistent with previous studies which suggest that NAC can chelate free iron and inhibit the iron-mediated cell death pathway, ferroptosis [74,82,83].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The lack of difference in total non-ferritin-bound iron observed between NAC, NAC + DFO and DFO pre-treatments suggests that NAC possesses some inherent iron chelator capacity. This is consistent with previous studies which suggest that NAC can chelate free iron and inhibit the iron-mediated cell death pathway, ferroptosis [74,82,83].…”
Section: Discussionsupporting
confidence: 93%
“…However, the combination with NAC in P68 + DQA nanocarriers enhanced the cellular antioxidant activity of DFO against both rotenone and ABAP by 425% and 99%, respectively. The ability of NAC to generally match or exceed the antioxidant capability of NAC + DFO at both concentrations may be because NAC not only acts as an antioxidant via the glutathione mechanism, converting hydrogen peroxide into water, but it can also chelate iron to some extent directly reducing the formation of hydroxyl via the Fenton reaction [74,82,83].…”
Section: Discussionmentioning
confidence: 99%
“… 28 the first sign of myocardial iron overload is diastolic dysfunction due to reduction of SERCA activity and impairment cardiomyocyte relaxation. Also Wongjaikam and colleagues 29 have shown that level of SERCA protein in the heart was significantly reduced in iron-overloaded rats. Thus, cardiomyocyte function and Ca 2+ handling are sensitive sensors of iron excess in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 92%
“…However, the ability of MET to protect the myocardium may be reduced over time, emphasising the need to incorporate alternative therapies as an adjunct to improve the endogenous antioxidant status of the diabetic heart. As such, studies have presented data reporting on the preventive properties of NAC in hyperglycaemia-induced oxidative stress [11,[32][33][34][35]. Dludla (2018) performed a systematic review confirming the ameliorative properties of NAC and highlighted that there is a scarcity of data reporting on the comparative effect of NAC with common glucose-lowering therapies on the diabetic myocardium [11].…”
Section: Discussionmentioning
confidence: 99%